Prince's gambit - Pacat, C. S. (Pacat, C. S. Captive prince trilogy, 2015)
With their countries on the brink of war, Damen and his new master, Prince Laurent, must exchange the intrigues of the palace for the sweeping might of the battlefield as they travel to the border to avert a lethal plot. Forced to hide his identity, Damen finds himself increasingly drawn to the dangerous, charismatic Laurent. But as the fledgling trust between the two men deepens, the truth of secrets from both their pasts is poised to deal them the crowning death blow ...